2021
DOI: 10.1055/a-1323-3050
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels and Adipose Tissue Gene Expression of Cathelicidin Antimicrobial Peptide (CAMP) in Obesity and During Weight Loss

Abstract: CAMP (Cathelicidin antimicrobial peptide) is synthesized and secreted by adipocytes and involved in adipose tissue (AT) innate immune response and host defense of subcutaneous AT against Gram positive bacteria. Data on the regulation of CAMP in obesity and during weight loss are scarce and reference values do not exist. Serum CAMP levels (ELISA) and AT gene expression levels (quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
(43 reference statements)
6
18
1
Order By: Relevance
“…Studies have shown that mice fed with a high-fat diet developed obesity and leptin resistance [ 68 ]. Importantly, Hochberg et al demonstrated in a human study that CAMP expression was negatively correlated with leptin level in subcutaneous adipose tissue of obese subjects undergoing a bariatric surgery [ 69 ]. It will be interesting to investigate how does the deficiency of CRAMP affect leptin expression and whether it can contribute to the protective effects on fatty liver in our animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mice fed with a high-fat diet developed obesity and leptin resistance [ 68 ]. Importantly, Hochberg et al demonstrated in a human study that CAMP expression was negatively correlated with leptin level in subcutaneous adipose tissue of obese subjects undergoing a bariatric surgery [ 69 ]. It will be interesting to investigate how does the deficiency of CRAMP affect leptin expression and whether it can contribute to the protective effects on fatty liver in our animal model.…”
Section: Discussionmentioning
confidence: 99%
“…EDNRB (endothelin receptor type B) [181], FGF10 [182], WNK3 [183], KNG1 [184], FCN3 [185], AQP3 [186], HPR (haptoglobin-related protein) [187], CTH (cystathionine gamma-lyase) [188], SPARCL1 [189], MAOA (monoamine oxidase A) [190], BMPR1B (bone morphogenetic protein receptor type 1B) [191], FGF7 [192], CALCRL (calcitonin receptor like receptor) [193], MARK3 [194], ADH1B [195], AMH (anti-Mullerian hormone) [196], RET (ret proto-oncogene) [197], IGF2 [198], SLC6A9 [199], NPPA (natriuretic peptide A) [200], SCT (secretin) [201], DCX (doublecortin) [202], ASIC1 [203], LMX1B [204], DBP (D-box binding PAR bZIP transcription factor) [205] and SLC6A9 [206] levels are correlated with disease severity in patients with hypertension. CAMP (cathelicidin antimicrobial peptide) [207], SPP1 [208]. CXCL11 [209], TFRC (transferrin receptor) [210], IRAK3 [211], C3AR1 [212], GLI2 [213], THY1 [214], FOXO6 [215], RGS4 [216], WNT10B [217] and AEBP1 [218] were found to be involved in progression of obesity, but these genes might be novel target for MI.…”
Section: Discussionmentioning
confidence: 99%
“…Murine 3T3-L1 preadipocytes were cultured at 37 °C and 5% CO 2 in DMEM (Dulbecco’s modified Eagle medium, Biochrom AG, Berlin, Germany) supplemented with 10% newborn calf serum (NCS; Sigma-Aldrich) and 1% penicillin/streptomycin (PAN-Biotech, Aidenbach, Germany). At confluence, the cells were differentiated into mature adipocytes by culturing in DMEM/F12/glutamate medium (Lonza, Basel, Switzerland) supplemented with 20 μM 3-Isobutylmethylxanthine (Serva, Heidelberg, Germany), 1 μM corticosterone, 100 nM insulin, 200 μM ascorbate, 2 μg/ml apo-transferrin, 5% fetal calf serum (FCS, PAN-Biotech), 1 μM biotin, 17 μM pantothenate, 1% penicillin/streptomycin, and 300 μg/ml Pedersen fetuin (MP Biomedicals, Illkirch, France) ( Zaitsu and Serrero, 1990 ; Bachmeier and Löffler, 1994 ) for 9 days using a slightly modified protocol as reported previously ( Hochberg et al, 2021 ). The cell cultures were supplemented with adipogenesis-inducing medium (AIM) from day 0 to day 8 of differentiation, when the cell culture medium was switched to serum-free conditions (with increased insulin supplementation to a concentration of 1 μM).…”
Section: Methodsmentioning
confidence: 99%